Adsorption and desorption of paraquat in acid tropical soils - Juo, A.S.R.; Oginni, O.O. (Wiley, 1978)
Adsorption of paraquat (1:1′-dimethyl 4:4′-bipyridylium chloride) by six common soil types from southern Nigeria was studied. Adsorption data conformed with linear Langmuir isotherm. Adsorption maximum (b) calculated from the Langmuir equation ranged from 1,200 to 7,500 µg/g of soil. The iron oxide-rich soil derived from basalts adsorbed the highest amount, while the strongly acidic soils derived from sedimentary rocks adsorbed the least amount of paraquat. Desorption data indicated that a substantial portion (40 to 70%) of the adsorbed paraquat could not be recovered by 12 successive extractions with dilute CaCl2 solution.